2018
DOI: 10.21660/2018.51.90835
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Model Pile Foundations in Seasonally Freezing Soil Ground

Abstract: ABSTRACT:The bearing capacity and settlement of pile foundation were greatly influenced by the temperature variations of soil ground around pile foundation. This paper presented a short report about laboratory static load tests by model precast concrete piles (cross-section 4 × 4 cm and length of 60 cm) in seasonally freezing soil ground. The depth of frozen soil was 10 cm, temperature -5℃, -10℃, +20℃. There were many factors influencing on pile foundations, such as ice in the ground, low temperatures and mois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This form of adaptation is important, specifically in dealing with tidal effects on soil water content and soil temperature. Meanwhile, several studies showed that changes in soil temperature affect the bearing capacity of the pile foundation [10,11]. Gelam wood is a leading commodity and a potential source of local government revenue when managed properly.…”
Section: Utilization Pattern and Potential Of Gelam Wood (Melaleuca C...mentioning
confidence: 99%
“…This form of adaptation is important, specifically in dealing with tidal effects on soil water content and soil temperature. Meanwhile, several studies showed that changes in soil temperature affect the bearing capacity of the pile foundation [10,11]. Gelam wood is a leading commodity and a potential source of local government revenue when managed properly.…”
Section: Utilization Pattern and Potential Of Gelam Wood (Melaleuca C...mentioning
confidence: 99%
“…The influence of temperature on the UBC of pipe piles cannot be ignored [28,29]. Based on the finite element model described in Section 4.1, a thermal load is applied on the pile surface and soil surface to transfer the temperature along the depth of the soil to study the variation in the pipe pile bearing capacity under the action of temperature.…”
Section: Influence Of Temperaturementioning
confidence: 99%
“…Clay is a finely grained material from natural rock and soil that consist of minerals such as hydrous aluminum and little traces of quartz, metal oxides and organic matter. The major content of geologic clay deposits is phyllosilicate minerals, which contain variable amounts of water found in its mineral structure [7,8]. The clay material used for the present study comes from the small city of Jingdezhen, Jiang Xi province, South East China.…”
Section: Claymentioning
confidence: 99%